Islamic economics : is it a doctrine or a science? - Furqani, Hafas (Penerbit Universiti Kebangsaan Malaysia, 2021)
The paper aims at reviewing the arguments of Islamic economics scholars in clarifying the nature of Islamic economics as a doctrine or a science. This papers attempts to integrate the two perspective of doctrine and scientific dimensions in Islamic economics. This is done by arguing that Islamic economics is developed based on Islamic doctrine on economics and attempts to manifest the doctrine in practical realities. It is found that the practical reality is actually the manifestation of doctrine, and vice versa, hence doctrine must find its foot in the practical realm. Therefore, Islamic economics as a discipline has a root in the Islamic doctrine of economics. It also has a scientific element because it studies the practical realities in the light of doctrine. This would implicate to the extension of the scope of Islamic economics as a science which is not only concern on normative judgments but also in empirical realm.